Jewish Universalism?: The Nations in the Rosh Hashanah Liturgy - Langer, Ruth (Studies in Christian-Jewish Relations, 2020)
Today’s positive relationship with Christians and Christianity challenges the voices of particularism in Jewish tradition. To discern how contemporary Jewish leaders are guiding their communities to think about the place of Jews within the larger human community, this article analyzes commentaries on a selection of Rosh Hashanah prayers from recently published prayer books commonly used in North American congregations. These prayers’ traditional texts themselves engage in a dialectic between universalism and particularism. The commentaries’ responses range along a spectrum, from an embrace of universalism by Reform Jews, to an advocacy also, but not exclusively, for particularism, among the orthodox.